Productivity and genetic variation of elite sugarcane (Saccharum officinarum L.) clones under dryland grumusol soil - Pertiwi, Riska Indah Guritno Gita; Budi, Setyo; Lailiyah, Wiharyanti Nur (Jurnal Ilmiah Pertanian, 2025)
Sugar production in Indonesia has declined in recent years, primarily due to climate change, extreme weather conditions, and the limited availability of high-yielding varieties. This study aimed to evaluate the productivity and genetic variation of seven elite sugarcane clones and two commercial varieties cultivated under dryland grumusol soil conditions. The research was conducted at PT Perkebunan Nusantara X, Sidoarjo, Indonesia, using a randomized block design (RBD) with nine treatments and three replications. Agronomic and yield-related parameters such as plant height, number of stalks, internodes, stalk weight, Brix value, sugar content, and crystal yield were measured. Data were analyzed using ANOVA followed by a 5% LSD test, and correlation analysis was conducted to assess inter-variable relationships. Results showed significant differences among clones in all measured traits. JW01 UMG NX exhibited the highest Brix value (24%), stem weight (106.4 tons/ha), and crystal yield (9.66 tons/ha), while SB20 UMG NX recorded the highest sugar content (9.46%). Positive correlations were observed between stalk weight and Crystal yield, while Brix values were negatively correlated with plant height. These findings indicate that the selected clones possess valuable agronomic traits and adaptability to dryland grumusol soil, making them strong candidates for future variety development